Loss of Malat1 does not modify age- or diet-induced adipose tissue accretion and insulin resistance in mice. - Sophie Carter; Stéphanie Miard; Louise Boivin; Sandrine Sallé-Lefort; Frédéric Picard (PLoS ONE, 2018)
Several studies have suggested that signals emerging from white adipose tissue can contribute to the control of longevity. In turn, aging is associated with perturbed regulation and partitioning of fat depots and insulin resistance. However, the exact mechanisms involved in these relationships remain undetermined. Using RAP-PCR on adipose tissue of young and old male mice coupled with qPCR validation, we have uncovered the long non-coding RNA Malat1 as a gene robustly downregulated in visceral white adipose tissue (vWAT) during normal aging in male mice and men. Reductions in Malat1 expression in subcutaneous WAT (scWAT) were also observed in genetic (ob and db) as well as diet-induced models of obesity. Based on these findings, Malat1+/+ and Malat1-/- mouse littermates were thus probed to detect whether loss of Malat1 would impact age or diet-induced gain in fat mass and development of glucose intolerance. Contrary to this hypothesis, male and female Malat1-deficient mice gained as much weight, and developed insulin resistance to a similar extent as their Malat1+/+ littermates when studied up to eight months old on regular chow or a high-fat, high-sucrose diet. Moreover, we observed no marked difference in oxygen consumption, food intake, or lipid profiles between Malat1+/+ and Malat1-/- mice. Therefore, we conclude that the overall metabolic impact of the absence of Malat1 on adipose tissue accretion and glucose intolerance is either physiologically not relevant upon aging and obesity, or that it is masked by as yet unknown compensatory mechanisms.